2019
DOI: 10.1136/bmjophth-2018-000242
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcomes following cataract surgery in patients who have had myopic laser vision correction

Abstract: ObjectivePrediction errors are increased among patients presenting for cataract surgery post laser vision correction (LVC) as biometric relationships are altered. We investigated the prediction errors of five formulae among these patients.Methods and analysisThe intended refractive error was calculated as a sphero-cylinder and as a spherical equivalent for analysis. For determining the difference between the intended and postoperative refractive error, data were transformed into components of Long's formalism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In addition, concerning the corneal tissue needed to perform a transplant, it is easier to employ refractive surgery [ 37 , 38 ]. Refractive surgery can also occasionally be used to alleviate adverse effects from other conditions, such as cataracts [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, concerning the corneal tissue needed to perform a transplant, it is easier to employ refractive surgery [ 37 , 38 ]. Refractive surgery can also occasionally be used to alleviate adverse effects from other conditions, such as cataracts [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately so far, most of the studies dealing with IOL power calculation with a and without previous refractive surgery did not consider the recommendations by Hoffer et al PLOS ONE [24,[41][42][43][44][45][46]. The reasons for this are different, some authors did not apply the zeroing of the mean error just for technical difficulties [47].…”
Section: Plos Onementioning
confidence: 99%
“…Hoffer et al suggested to avoid multiple IOLs in a study when reporting a method accuracy [24]. This is acceptable but obtaining a large database in most of the studies regarding IOL power calculation after refractive surgery is difficult, hence multiple IOL models were analyzed [22,25,[41][42][43][44]. As reported by Abulafia et al [48] more than one IOL model is appropriate when limited data are available.…”
Section: Plos Onementioning
confidence: 99%
“…Implantation of multifocal IOLs after LASIK has remained controversial because of concerns that the corneal higher-order aberrations (HOAs) combined with the dysphotopsia of multifocal implants will significantly impact the quality of vision despite considerable improvements in postcorneal refractive surgery IOL calculations. 12 The risk of obtaining an undesirable refractive outcome from an IOL surprise still continues to discourage some surgeons from pursuing multifocal IOLs in post-LASIK cataract patients.…”
mentioning
confidence: 99%